IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS QUESTIONS ON STUDENTS’ TEXTBOOKS - Siti Aulia Rohmawati; Mujimin (Universitas PGRI Palembang, 2025)
The application of Higher Order Thinking Skills (HOTS) in the questions of the Gayeng Javanese Language textbook is essential to assess the feasibility of the textbook. One of the indicators for evaluating the feasibility of a textbook in the learning assessment component is the presence of an evaluation format, including worksheets, activity sheets, and HOTS-based practice questions. Therefore, this study aims to describe the implementation of HOTS in both formative and summative assessment questions in the Gayeng Javanese Language Class X textbook, published by Media Karya Putra. This study uses a qualitative approach with a descriptive method and a data card instrument in the form of a table, with data collection techniques based on document review using reading and note-taking techniques. Based on the data analysis, the study shows that the implementation of HOTS in Formative Assessment and Summative Assessment is divided into cognitive level C4, categorized as 'describing', 'organizing', and 'finding implied messages', and cognitive level C5, categorized as 'checking' and 'criticizing'. However, the textbook does not include cognitive level C4 categorized as 'describing', cognitive level C5 categorized as 'criticizing', nor cognitive level C6.